Content arrangement characteristic based encryption in cloud using public auditing for data management - Jerard, V. Joseph Michael; Manimegalai, P. (International Journal of Engineering and Technology, 2017)
The encryption standard related to cryptography provide the possible keys with logical standard for sharing and distributing sensitive information sharing worldview in conveyed frameworks. A Content Arrangement Characteristic Based Encryption (CA-CBE) is turning into a promising cryptographic solution for this issue.Â  The cloud needs to provide the view on open auditability. Many methodologies have been discussed on dynamic information administration and on general auditability, however those methodologies suffer from the issue of check overhead and time multifaceted nature. Therefore, it is important to propose a Content Arrangement Characteristic Based Encryption (CA-CBE) scheme for supporting data dynamics over the data operation, like block alteration, block inset, and deletion. Some existing data integrity based research always lacks in dynamic operations and public auditability. By considering this as a motivation, this research is initiated.Â